"The Future of Libraries:" Vocational Awe in a "Post-COVID" World. Issue 1 (1st May 2022) - Ettarh, Fobazi; Vidas, Chris
ABSTRACT: Fobazi Ettarh presented a cautionary tale regarding the future of libraries in her Vision Session at the 2021 NASIG Conference. Rather than painting an unrealistically optimistic picture of the future, Fobazi highlighted numerous concerns surrounding libraries and the increasingly lofty demands placed on library workers. Between the pandemic and growing societal concerns surrounding race and equity, libraries need to unite to form a better future that emphasizes individual care and self-love which will ultimately go further in achieving goals that positively impact the communities they serve.